Management Of Drug Use In Patients With Febrible Seizures In Palaraya Mother And Child Hospital, Tegal District - Sari Prabandari; Meliyana Meliyana (Sean Institute, 2023)
Pharmaceutical preparation management, especially drug management, is one of the most critical activities that receive an allocation of 40-50% of funds. Drugs must be managed optimally to ensure the achievement of the correct number and type of pharmaceutical supplies that are sufficient and appropriate for their use. This study aims to provide the availability of drugs, whenever needed, in terms of style, amount, and proper usage, effectively and efficiently in pediatric patients with febrile seizures. Febrile seizures are seizures associated with symptoms of fever and age, and there is no intracranial infection or other abnormalities in the brain. This type of research is a qualitative descriptive study to determine drug management in the Pharmacy Installation of Palaraya Mother and Child Hospital in the Tegal Regency. In this study, researchers used a qualitative approach to obtain more in-depth information about managing drugs used in patients with febrile seizures in hospital pharmacy installations. The sampling method in this study was total sampling, namely outpatients from July to September 2022 at Pala Raya Hospital who were diagnosed with febrile seizures and met the inclusion and exclusion criteria. The method of collecting data is using secondary data obtained by recording the name of the drug in the patient's medical record from July to September 2022 on a worksheet.